Aplikasi Mobile Augmented Reality Pada Proses Terjadinya Gerhana Matahari - Ismail, Taufiq; Muda, Lalu Iskandar (STIKOM Tunas Bangsa Pematangsiantar, 2021)
One of the interesting cosmic phenomena to study in astronomy is solar eclipses because they are so rare that observations are recommended. This study developed a mobile application as a medium to explain the process of a solar eclipse using Augmented Reality with equipment such as a telescope, sun glasses, and pinhole. The application was built in collaboration with the Andromeda Study Group and the Ahmad Dahlan University Center for Astronomy Studies. The method used in this research is the Multimedia Development Life Cycle (MDLC) which consists of six stages, namely concept, design, material collection, assembly, testing, and distribution. This study produces a mobile application for the introduction of a solar eclipse using Augmented Reality to help people understand the process of a solar eclipse digitally or in 3D. Applications that have been made in this study are then tested using the blackbox test and material feasibility test. The blackbox test produces a value of 100% so that the application built can function properly. The feasibility test produces a value of 100% so that it is declared that the application is suitable for use.